Triggers for Atrial Fibrillation: The Role of Anxiety - Paolo Severino; Marco Valerio Mariani; Annalisa Maraone; Agostino Piro; Andrea Ceccacci; Lorenzo Tarsitani; Viviana Maestrini; Massimo Mancone; Carlo Lavalle; Massimo Pasquini; Francesco Fedele (Cardiology Research and Practice)
Atrial fibrillation (AF) is the most widely recognized arrhythmia. Systemic arterial hypertension, diabetes, obesity, heart failure, and valvular heart diseases are major risk factors for the onset and progression of AF. Various studies have emphasized the augmented anxiety rate among AF patients due to the poor quality of life; however, little information is known about the possibility of triggering atrial fibrillation by anxiety. The present review sought to underline the possible pathophysiological association between AF and anxiety disorders and suggests that anxiety can be an independent risk factor for AF, acting as a trigger, creating an arrhythmogenic substrate, and modulating the autonomic nervous system. The awareness of the role of anxiety disorders as a risk factor for AF may lead to the development of new clinical strategies for the management of AF.